Soil degradation and feedback processes affect long‐term recovery of tropical secondary forests. (15th April 2016) - Chua, Siew Chin; Ramage, Benjamin S.; Potts, Matthew D.
Abstract: Questions: What processes govern the long‐term recovery of tropical secondary forests? Specifically, how are seedling species density, stem density and functional groups in older regenerating forests affected by existing trees, the regeneration environment and distance to seed sources? Location: Central Catchment Nature Reserve, Singapore. Methods: We investigated three primary forest plots and nine 60‐yr‐old secondary forest plots varying in their degree of recovery. We analysed seedling parameters as a function of the abiotic and biotic regeneration environment as well as distance to primary and mature secondary forests. Results: The secondary forest plots had functional composition distinct from, and Chao‐estimated species richness and stem density lower than the primary forest plots. Seedling communities were most strongly associated with the mature tree communities within each plot; associations with other intra‐plot variables and distance to potential seed sources were lower but still highly significant. Overall, aside from the mature tree community, the most significant predictors of seedling species composition were fern cover, VPD, soil Al, available P and C:N ratio. Primary forest species were associated with low light environments, low macronutrients and low Al saturation. Secondary forest species were associated with high P, low soil pH and low total exchangeable bases. Long‐lived pioneers differed from short‐lived pioneers in their association with high soil C:N ratio, low Al saturation, low P and tolerance of a wider light range. Overall, improved seedling recruitment was associated with decreasing fern cover, thinner layer of leaf litter and higher light. At the landscape level, species density was inversely related to distance to potential seed sources. Conclusions: Our findings suggest that historical soil degradation and subsequent feedback processes among the adult trees, seedling communities and the regeneration environment strongly affect forest succession. Nutrient‐efficient and Al‐tolerant pioneers, such as the fern Dicranopteris linearis, were probably initial colonizers. Chance dispersal and recovery of the regeneration environment subsequently affected the establishment of long‐lived or short‐lived pioneers. Persistence of D. linearis and long‐lived pioneers slowed forest recovery, while short‐lived pioneers improved nutrient recovery and ameliorated the above‐ground conditions to facilitate subsequent succession, provided that seeds of primary forest species were present. Abstract : This study examined the dynamics and regeneration of older tropical secondary forests. We adopted a process‐based approach to understand the drivers of community assembly in these forests, by characterizing the existing site conditions and using that to model seedling recruitment. We found that land use history could initiate a series of events that have long lasting effects on tropical succession. The photo shows a representation of the open vegetation (class O) found in the regenerating forests of Central Catchment Nature in Singapore, even after more than 60 years of natural regrowth.